Use of guanidine compounds in the treatment of neglected tropical diseases - do Espírito Santo, Rafael D. [UNESP]; Machado, Marcella G. M. [UNESP]; dos Santos, Jean L. [UNESP]; González, Eduardo R. P. [UNESP]; Chin, Chung M. [UNESP] (My University, 2014)
Over one billion people worldwide are afflicted by a group of 17 infectious diseases, known as the neglected tropical diseases (NTDs), reaching mainly undeveloped countries that suffer with a lack of economic incentive, research and policy for new drug discovery. Compounds with guanidine moiety are privileged structures and are attractive as scaffold for the discovery of new drug candidates. This functional group is an important pharmacophore moiety in several therapeutically active compounds. Guanidine-containing heterocycles have been reported to exhibit different biological properties including antiprotozoal and antiparasitic activity such as mebendazole and pyrimethamine used in current therapeutics. The present review covers the progress of guanidine derivatives for NTDs (Human African Trypanosomiasis, Chagas Disease, Leishmaniasis, Buruli Ulcer, Echinococcosis, Taeniasis/Cysticercosis, Lymphatic Filariasis and Onchocerciasis). Also, review the development of new guanidine derivatives in Malaria and Tuberculosis.
Keywords: Antiparasitic; Antiprotozoal; Guanidine; Guanidine derivatives; Neglected tropical diseases